Legal Controls on Child Labor in International Conventions and National Legislation - Ahmed, Dr. Sirwan Hamd; Ameen, Rizgar Abdul Mohamed (Journal of Legal and Political Studies, 2018)
Child labor is considered as one of the most sensitive issues of international and domestic law because it is directly related to the work of children who need mental, psychological and physical care. Any legal regulation in this field that does not take into consideration this aspect will have a negative impact on society. After the international community's failure to successfully prohibit child labor, their efforts focused on finding some restrictions on the employment of children, in particular determining the quality of work that children are allowed to do so that they do not have negative effects on their mind, psyche, and body. At the same time they tried to identify the minimal age for work as they have obliged those who operate the children to conduct a preliminary and periodic medical examination on an ongoing basis to determine the extent of the children's physical ability to perform any work. On the other hand, the employment of the children should not lead to their deprivation of education.
Keywords: domestic law; physical care; international community; medical examinatio; restrictions